Tratamiento de aguas residuales mediante un sistema de lagunas anaerobias para el sitio la florida de la parroquia bellavista - Ruilova Rebilla, David Alejandro (2017)
The growth of the urban sector has been a very important factor in the increase of water supply in the last decades, thus causing overexploitation and pollution of this natural resource. Wastewater contains pathogenic organisms that can cause many diseases such as diarrhea, cholera and malaria among others. Therefore, these waters are considered very dangerous for living beings when discarded on the surface of the soil, underground or in a riverbed. Wastewater is made up of 99% water and 1% solids dissolved, suspended or colloidal. To determine the selection of an appropriate wastewater treatment system flows immensely in the nature of raw wastewater and future uses of the tributary Which contributes to the care of human health and the environment. In Florida 1, located in the Bellavista parish, sewage is generally deposited in septic tanks and then discharged without prior treatment to the Arenillas River. This activity on a daily basis poses a great risk to health and a negative impact on the environment, contaminating the tributary of the Arenillas river. Therefore, the objective of this research is to develop an alternative design of wastewater treatment by means of an anaerobic lagoon system for small supply networks, the pond system are ponds designed for the treatment of wastewater through natural biological processes, the Use of this type of treatment is especially recommended when a high degree of removal of pathogenic organisms is required. These treatment processes are selected because they are of low investment, operation and maintenance costs In addition, due to its high efficiency of removal of organic matter measured in Dbo5, the type of field, applied and laboratory research was applied to select the alternative of the prototype to be designed. In field research we can know the sector's problems through the different opinions of the inhabitants, in applied research we will seek knowledge with direct application to the sector's problems, which is based mainly on design criteria for wastewater treatment For small localities that exist in different parts of the world. In the laboratory investigation was carried out infiltration tests proposed by Elías Rosales Specialist in Sanitary Engineering of the Institute of Hydraulics and Environmental to determine the type of soil of the sector, for the design of the prototype was realized by the method of Marais, receiving us of the criteria Of the Pan American Center for Sanitary Engineering and Environmental Sciences (CEPIS) and the regulations of the Ecuadorian Code for the Design of Sanitary Works Construction. The results obtained by the application of the Marais method obtained a total retention period of 13 days with 15 hours with a removal efficiency of 99.86%, a total area of 4400 m2 (0.44 ha). With regard to the soil in the tests performed we obtained a waterproof floor where the waterproof layer begins at 2.00 m. For this reason the sector if it is in conditions for the prototype of design by anaerobic lagoons posing for the treatment of waste water. Since the anaerobic lagoons can be designed with a depth of 2.00 m to 5.00 m which favors the realization of the prototype in investment costs.